2021
DOI: 10.3847/1538-4365/ac0f0a
|View full text |Cite
|
Sign up to set email alerts
|

The Magellan-TESS Survey. I. Survey Description and Midsurvey Results* †

Abstract: Kepler revealed that roughly one-third of Sunlike stars host planets orbiting within 100 days and between the size of Earth and Neptune. How do these planets form, what are they made of, and do they represent a continuous population or multiple populations? To help address these questions, we began the Magellan-TESS Survey (MTS), which uses Magellan II/PFS to obtain radial velocity (RV) masses of 30 TESS-detected exoplanets and develops an analysis framework that connects observed planet distributions to under… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 161 publications
0
23
0
Order By: Relevance
“…However, when Otegi et al (2020a) curated a high-fidelity sample of exoplanet mass and radius measurements from the We only include planets with better than 15% fractional measurement precision in radius and 33% fractional precision in mass. We note that the sample of planets shown here may lack completeness for low-density sub-Neptunes due to our fractional precision requirements, but they should not impact completeness at high density (Burt et al 2018;Montet 2018;Teske et al 2021). Planets and their 1σ measurement uncertainties are colored by equilibrium temperature assuming zero Bond albedo.…”
Section: Kepler-145 Bmentioning
confidence: 82%
See 1 more Smart Citation
“…However, when Otegi et al (2020a) curated a high-fidelity sample of exoplanet mass and radius measurements from the We only include planets with better than 15% fractional measurement precision in radius and 33% fractional precision in mass. We note that the sample of planets shown here may lack completeness for low-density sub-Neptunes due to our fractional precision requirements, but they should not impact completeness at high density (Burt et al 2018;Montet 2018;Teske et al 2021). Planets and their 1σ measurement uncertainties are colored by equilibrium temperature assuming zero Bond albedo.…”
Section: Kepler-145 Bmentioning
confidence: 82%
“…While we found that our mass measurement for K2-182 b was consistent between RV models with and without a GP trained on the K2 photometry, we suggest that additional monitoring will better inform the influence of stellar activity on the spectroscopic observations. Furthermore, cases where starspots contribute to planet RV amplitude may be subject to publication bias because the inflated signal can more easily overcome standard fractional precision thresholds, like M p s  5 M p (Burt et al 2018;Montet 2018;Batalha et al 2019;Teske et al 2021).…”
Section: Superdense Sub-neptunesmentioning
confidence: 99%
“…There are several ongoing, ground-based TESS RV surveys, e.g., MTS (Teske et al 2021), NCORES (Armstrong & consortium 2021), KESPRINT (Kabath et al 2021), etc., many of which have science interests that overlap with those of TKS. Our target selection procedure was strategically implemented to achieve the most optimal sample that simultaneously addressed the different science goals within the survey (see Section 5 for more details).…”
Section: Coordination With Other Surveysmentioning
confidence: 99%
“…Therefore, a critical ingredient for the realization of these surveys is understanding the process by which targets were initially selected. Indeed, recent groundbased TESS follow-up programs such as the Magellan-TESS Survey (MTS; Teske et al 2021) have begun to describe target selection functions, providing a pathway to properly correct for survey biases or incompleteness.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the relatively large TESS pixels spanning 22″ on the sky, fainter visual eclipsing binaries can blend with the nearby bright target stars and produce false positives (barring instrumental artifacts). This is an important consideration, particularly when only a single transiting planet is found in the TESS 27 day time baseline of sector observations, at lower ecliptic latitudes, and away from the ecliptic poles (Lissauer et al 2012;Vanderburg et al 2019;Rodríguez Martínez et al 2020;Hobson et al 2021;Addison et al 2021;Osborn et al 2021;Dreizler et al 2020;Brahm et al 2020;Nowak et al 2020;Teske et al 2020;Sha et al 2021;Gan et al 2021;Bluhm et al 2020).…”
Section: Introductionmentioning
confidence: 99%